NEW AGE BELIEFS OF DIGITAL NATIVE STUDENTS - BOZDAĞ TULUM, Arzu (SSD Journal, 2023)
In this research; it is aimed to determine whether the young generation expressed as “Digital Native” has new age beliefs, to analyse these beliefs in terms of socio-demographic variables, to present the psycho-social reasons behind these beliefs and to contribute to the literature.In this research, mixed research method was used. While in-depth interview technique was used from qualitative techniques, survey technique was used from quantitative techniques The population of the study consists of students who have the characteristics of “Digital Native” and continue their education at high school level in 5 different types. In this context, a total of 206 students were identified as the research sample. The main data sources of the research are the participant information form including the socio-demographic characteristics of the participants and the “New Age Beliefs Scale” developed by Kaya and Mevlüt. The data obtained in the study were analysed using SPSS 25. In the analyses, firstly, the socio-demographic characteristics of the participants and then the levels of “New Age Beliefs” were determined. In addition, in order to determine whether the socio-demographic characteristics of the participants create a significant difference with the levels of “New Age Beliefs”, frequency distributions, percentage and mean score values were determined and T test and Anova analyses were performed. In addition to these quantitative data, in-depth interviews were conducted with 20 participants. In-depth interviews were recorded and then transcribed and written down. All the data obtained were interpreted together and included in the research. As a result of the research, it was found that “Digital Native” participants had moderate levels of “New Age Beliefs”. However, among the sub-dimensions of “New Age Beliefs”; “Old Folk Beliefs and Predicting the Future” sub-dimension scores were found to be low, while “Spiritism and Psychic Powers” and “Healing Objects and Methods” sub-dimensions scores were found to be high. In the study, it was observed that “New Age Beliefs” made a difference in terms of sociodemographic variables; school type and the place where they spent most of their lives.